COENOFLORA PULSATILLA PATENS (L.) MILL. s.l. IN NORTHERN KAZAKHSTAN - G. J. Sultangazina; О. А. Kuprijanov; А. N. Kuprijanov; R. S. Beyshov (Scientific Journal of Pedagogy and Economics, 2019)
The current article presents the results of the study made on Pulsatilla patens (L.) Mill. s.l. coenoflora of Northern Kazakhstan. The materials have been obtained in the course of field research considering the literary data. The list of pulsatilla flora discovered in Northern Kazakhstan is based on detailed route studies. The coenoflora of Pulsatilla patens (L.) Mill. s.l. in Northern Kazakhstan includes 168 species belonging to 42 families and 141 genera. The leading families are Asteraceae, Poaceae, Rosaceae, Fabaceae, Caryophyllaceae, Ranunculaceae. The largest number of species refers to perennial species (150), annuals and biennials make up 15 species, ephemera - 3 species. Among the life forms, there are mainly long-rooted (70) and stem-rooted (36) species. The coenoflora has a steppe character with a small number of forest floristic elements correlating with ecological conditions of the rocky (and partly sparsely forest) habitats where the populations are formed. The eco-biological analysis confirmed a meadow-steppe character of coenoflora. Anthropogenic breach of coenoflora is expressed in a rather large number of weed species (18 species - 11%).